2009
DOI: 10.3109/10428190903308007
|View full text |Cite
|
Sign up to set email alerts
|

Primary bone lymphoma – the University of Miami experience

Abstract: Primary bone lymphoma (PBL) is a rare disease. There has been paucity of studies addressing its therapy and prognosis. We retrospectively examined PBL cases seen at the University of Miami from June 2000 to August 2007 to describe our single institution experience and review the literature. Fifty-three patients were identified with a median age of 52 (18-87) and a median follow-up of 40 months (0-106). The most common histologic type was diffuse large B-cell lymphoma (83%). Forty-one patients (77%) presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
53
5
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 49 publications
12
53
5
2
Order By: Relevance
“…Considering current studies and several previously-published studies, patients treated with chemoradiotherapy appeared to present an improved outcome compared with patients receiving single modality therapy (25)(26)(27)(28)(29). These observations require confirmation by prospective studies with larger sample groups, since specific studies appear to disprove them (2,26,27,33,34). For instance, in the IELSG-14 study, the addition of radiotherapy following chemotherapy, or the use of larger radiation fields and doses, were not associated with an improved outcome in patients treated with chemoradiotherapy (9).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Considering current studies and several previously-published studies, patients treated with chemoradiotherapy appeared to present an improved outcome compared with patients receiving single modality therapy (25)(26)(27)(28)(29). These observations require confirmation by prospective studies with larger sample groups, since specific studies appear to disprove them (2,26,27,33,34). For instance, in the IELSG-14 study, the addition of radiotherapy following chemotherapy, or the use of larger radiation fields and doses, were not associated with an improved outcome in patients treated with chemoradiotherapy (9).…”
Section: Discussionmentioning
confidence: 87%
“…Although previous studies have obtained contradicting results, chemoradiotherapy is likely to be superior to single modality therapy, which may be advantageous for localized unifocal bulky sites of disease, which allows a shorter chemotherapy course (1,30,35), or for multifocal disease in relapsing cases (36). Anthracycline-containing chemotherapy has become the standard therapy of DLBCL, while numerous studies have demonstrated increased long term remission rates with the incorporation of rituximab (33,(37)(38)(39)(40)(41)(42). Based on the aforementioned findings, chemotherapy plus rituximab (immunochemotherapy) is currently considered to be the first-line treatment for CD20-positive DLBCLs.…”
Section: Discussionmentioning
confidence: 99%
“…Persisting radiological abnormalities after treatment is a common finding in bone lymphomas and it does not prevent assessment of a remission state, which is evaluated upon the disappearance of local and systemic signs of lymphoma [5,11]. One patient achieved partial remission.…”
Section: Resultsmentioning
confidence: 99%
“…Ann Arbor stage I and stage II disease [3]; a lymphoma with the above-mentioned pattern can be considered a primary lymphoma of bone, as well as when involvement of bone marrow is present at diagnosis, i.e. Ann Arbor stage IV [4,5]. Due to the rarity of the disease, few series are reported in the literature, and only retrospective multicentre reviews involve high numbers of patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation